Porous low k film with multilayer structure used for promoting adhesion to SiCN cap barrier layer. Issue 6 (May 2015) - Zhou, M.; Zhang, B.C.
Highlights: The interfacial adhesion is weak between p-ULK and the underlying SiCN. p-ULK film has the multilayer structure for improving adhesion. Interfacial adhesion was improved by inserting initial oxide film and transition film. Abstract: For 28 nm technological node, porous ultra low dielectric constant (p-ULK) film has been used as an insulator in Cu interconnection in the back-end of the line (BEOL). The interfacial adhesion between p-ULK film and SiCN (nitrogen doping silicon carbon) cap barrier layer played the important role for the package, wiring bond, chip package interaction (CPI), peeling, and reliability. In this work, the thin initial oxide and thin transition films were deposited in situ before depositing p-ULK film, which was used for improving the interfacial adhesion between p-ULK film and SiCN film, The ULK film with multilayer structure was characterized by secondary ion mass spectroscopy (SIMS) for examining multilayer structure, focused ion beam (FIB) and transmission electron microscope (TEM) for observing interface, and four-point bending (4-PB) for testing interfacial adhesion. Results indicated that the interfacial adhesion was obviously improved by adding initial oxide and transition layer before the deposited p-ULK film, which hardly impact the capacitance using single layer structure.